Africans in India : from slavery to royalty - Chauhan, R. R. S. (New Delhi : Asian Publication Services, 1995)
Refers to the Siddhi, tribe from India; chiefly covers the period, 1 7th century to 1947.
Keywords: Siddi (Indic people -- Politics and government; India -- Politics and government -- 1765-1947.